Penggunaan Waktu Belajar Terhadap Prestasi Belajar Mahasiswa Prodi Teknik Sipil Fakultas Teknik UNIMA - Tulaka, Titof (Jurnal Ilmiah Wahana Pendidikan, 2025)
The use of study time is very important in successfully improving student learning achievement. The purpose of this study is to how the use of study time affects the learning achievement of Civil Engineering Study Program students, Faculty of Engineering Unima, How is the Learning Achievement of Civil Engineering Study Program students, Faculty of Engineering Unima, and is there an influence between the use of study time on the learning achievement of Civil Engineering Study Program students, Faculty of Engineering, Mando State University. The method used in this study is observation with a qualitative and descriptive approach to obtain an overview of the use of study time on student learning achievement. This approach emphasizes the role of the researcher as the main instrument in understanding the nature of the subject. Data collection methods involve triangulation, data analysis that has an inductive nature, and focus on meaning rather than generalization. The results of the data analysis obtained for the use of study time are 35 students (62.8%) with the category of sufficient use of study time while for the learning achievement of Civil Engineering Study Program students, Faculty of Engineering Unima is in the very satisfactory category with the results of 15 students (37.2%) and there is a relevant relationship if the use of study time students of Civil Engineering Study Program, Faculty of Engineering Unima is less, the lower the achievement index achieved value with a significance level (p) of 0.010.